The role of service empathy and assurance in building customer loyalty in the Nigerian road transport industry - Madumere Humphrey Ikenna; Cletus I. Emeti; Agu Godswill Agu; Nwaizugbo Ireneus Chukwud (Yayasan Ahmar Cendekia Indonesia, 2021)
Basing on the RATER model of service quality, we explored the role service empathy and assurance in building road transport customers’ loyalty intention. Being a quantitative study, data from 318 valid responses, analyzed with simple regression analysis in SPSS 21.0, indicate that the two constructs – service empathy and service assurance are positive and significant predictors of customer loyalty. Further, with 82% and 78.8% variance explained for assurance and empathy respectively, results indicate that service assurance drives more customer loyalty than service empathy in the organized road transport industry in Nigeria. To attract and retain customers, operators in the industry must be service quality conscious.